Evaluación de la toxicidad del extracto acuoso de hojas de Tessaria integrifolia R. et. P. sobre órganos de Rattus novergicus var. albinus - Bardales Chavez, Sandra Fiorella (2018)
The objective of the present work was to evaluate the toxicity of the aqueous extract of leaves of Tessaria integrifolia R. et. P. on organs of Rattus novergicus var. albinus, using the oral toxicity model at repeated doses for 28 days (toxicity test 407 of the guidelines of the Organization for Economic Cooperation and Development - OECD). 20 specimens Rattus novergicus var. albinus in 2 experimental groups of 10 specimens each (5 of each sex). Control Group: Physiological saline solution (0.9% SSF) was administered. Problem group: The leaf extract of Tessaria integrifolia R. et. P. at a dose of 500 mg/kg/day orally, administration was performed at 8:00 a.m. during the 28 days that the specimens received the treatments. At the end of the experience, euthanasia was performed with sodium pentobarbital 200 mg/kg intraperitoneally from the specimens and the organs were extracted, which were preserved in 10% formaldehyde for 8 days to perform the histopathological study. The results show that the brain, heart, kidneys, testes and ovaries of the problem group presented mild congestion, the stomach presented a moderate inflammatory infiltrate, the liver showed a slight congestion in the central vein and infiltration of the portal space, the lungs evidenced mild congestion, dilated and emphysematous alveoli and inflammatory infiltration; these results differ from the control group that did not show pathological alteration in the organs analyzed. In addition, a preliminary phytochemical study was conducted to identify its main phytoconstituents, determining the presence of flavonoids, phenolic groups, sesquiterpene lactones, saponins and tannins